2023
DOI: 10.1101/2023.04.06.23288258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“A System Dynamics Model for Long-term Aspect of Caries Preventive Interventions”

Abstract: Objective: The purpose of the study is to appraise the long-term effects of caries preventive interventions of the Ministry of Public Health (MOPH), Thailand: supervised toothbrushing (STB), dental sealant, and combined STB+sealant that are implemented for 6- to 15-year-olds by comparing with the base case using the System Dynamics Model (SDM). Method: The System Dynamics Model (SDM) was analyzed to compare the interventions, supervised toothbrushing (STB), sealant, and combined STB+sealant as intervention sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Our findings through the building block approach correspond to other studies of Myanmar (Sommanustweechai et al, 2016;Ei et al, 2019;Oo et al, 2021). One study reviewed the oral healthcare system in Myanmar using six building blocks and found low utilisation of oral healthcare services, lack of workforce, inadequate budget with non-transparent expenditure, and insufficient supply (Saw et al, 2019).…”
Section: Human Resourcessupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings through the building block approach correspond to other studies of Myanmar (Sommanustweechai et al, 2016;Ei et al, 2019;Oo et al, 2021). One study reviewed the oral healthcare system in Myanmar using six building blocks and found low utilisation of oral healthcare services, lack of workforce, inadequate budget with non-transparent expenditure, and insufficient supply (Saw et al, 2019).…”
Section: Human Resourcessupporting
confidence: 86%
“…Several study participants complained about the mismatches between the supply and demand of non-communicable disease medicine, implying a poor information system for medication management. In this regard, the Ministry of Health and Sports in Myanmar is currently developing an electronic information system and putting the effort into the overall readiness for this technology (Oo et al, 2021).…”
Section: Health Information Systemmentioning
confidence: 99%
See 1 more Smart Citation